Aztreonam, Ceftazidime/Avibactam, and Colistin Combination for the Management of Carbapenemase-Producing Klebsiella Pneumoniae Bacteremia: A Case Report. (August 2021) - Shah, Punit J.; Tran, Thuytram; Emelogu, Francis; Tariq, Farheen
Purpose: A case of a patient with sepsis from a urinary source due to carbapenemase-producing Klebsiella pneumoniae treated with a novel combination of aztreonam, ceftazidime/avibactam, and colistin is described.Summary: An 80-year-old South Asian male presented to the hospital with sepsis from a urinary source. Blood and urine cultures were positive for a carbapenemase-producing K pneumoniae sensitive only to colistin and tigecycline. Novel beta-lactamase inhibitor combinations ceftazidime/avibactam and meropenem/vaborbactam were resistant. Patient was initially on ceftazidime/avibactam and colistin combination followed by tigecycline and colistin with lack of improvement. Metallo-beta-lactamase (MBL)-producing K pneumoniae was suspected based on the sensitivity pattern and history of medical treatment in India. Patient was then initiated on novel combination of ceftazidime/avibactam, aztreonam, and colistin. Patient's white blood cell (WBC) count and fever curve normalized. Unfortunately, the patient failed to recover completely likely because of his multiple comorbidities and declining functional status, resulting in the family's decision to pursue hospice. Conclusion: The combination of ceftazidime/avibactam and aztreonam should be considered as a viable treatment option for patients with infections caused by MBL-producing Enterobacteriaceae.